Removal of direct navy blue dye from aqueous solutions using banana peels - F. Fuentes Gandara; I. Piñeres Ariza; A. Zambrano Arevalo; G. Castellar Ortega; C. Herrera Herrera; S. Castro Muñoz; G. Peluffo Foliaco; J. Pinedo-Hernández (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The textile industry is known to produce large amounts of dyes and other harmful contaminants. This issue is of great importance as it adversely affects both water resources and the well-being of organisms. To address this issue, biochar is frequently used as a sustainable and environmentally friendly material for removing chemical contaminants during wastewater treatment. The aim of this study was to evaluate the viability of utilizing biochar obtained from banana peels as a promising bioadsorbent for reducing environmental pollution caused by direct navy blue dye. The research investigated various factors such as temperature, potential of hydrogen levels, particle size, and concentrations to determine the effectiveness of biochar in dye removal.METHODS: The biochar obtained was separated into powdered and granular forms based on particle sizes of 425 and 850 micrometer, respectively. The biochar's textural characteristics were assessed through nitrogen adsorption/desorption isotherms. Fourier transform infrared spectroscopy and the Boehm method were employed to analyze and measure organic functional groups, specifically acidic groups, for identification and quantification purposes. Batch experiments were performed to ascertain the effects of the initial concentration and potential of hydrogen on the adsorption capacity and removal percentage.FINDINGS: The results indicated that the powdered biochar obtained at 500 degrees Celsius had the higher surface area, with a value of 80.4 square meter per gram. The biochar demonstrated remarkable removal percentages, achieving 97 percent at the lowest concentration and 89 percent at the highest concentration, when the potential of hydrogen was adjusted to a value of 6. The Freundlich model gave the best fit to the experimental data for this biochar and obeyed pseudo second order kinetics, with correlation coefficients of 0.93 and 0.99, respectively.  CONCLUSION: This study provides evidence of the high removal efficiency achieved by biochar derived from banana peel waste in the removal of direct navy blue dye. Precise temperature control during the calcination process is essential to ensure its favorable chemical and textural properties. The unique attributes of banana peel biochar position it as an exceptionally promising adsorbent material. Not only is it cost-effective and environmentally friendly, but it also outperforms current wastewater treatment technologies in terms of competitiveness. Its remarkable ability to reduce contaminants, particularly the removal of dyes, further solidifies its potential as a highly effective solution.